Multiple sclerosis patients have a distinct gut microbiota compared to healthy controls - Chen, Jun; Chia, Nicholas; Kalari, Krishna R; Yao, Janet Z; Novotna, Martina; Paz Soldan, M Mateo; Luckey, David H; Marietta, Eric V; Jeraldo, Patricio R; Chen, Xianfeng; Weinshenker, Brian G; Rodriguez, Moses; et al. (Scientific reports, 2016)
Multiple sclerosis (MS) is an immune-mediated disease, the etiology of which involves both genetic and environmental factors. The exact nature of the environmental factors responsible for predisposition to MS remains elusive; however, it's hypothesized that gastrointestinal microbiota might play an important role in pathogenesis of MS. Therefore, this study was designed to investigate whether gut microbiota are altered in MS by comparing the fecal microbiota in relapsing remitting MS (RRMS) (n = 31) patients to that of age- and gender-matched healthy controls (n = 36). Phylotype profiles of the gut microbial populations were generated using hypervariable tag sequencing of the V3-V5 region of the 16S ribosomal RNA gene. Detailed fecal microbiome analyses revealed that MS patients had distinct microbial community profile compared to healthy controls. We observed an increased abundance of Psuedomonas, Mycoplana, Haemophilus, Blautia, and Dorea genera in MS patients, whereas control group showed increased abundance of Parabacteroides, Adlercreutzia and Prevotella genera. Thus our study is consistent with the hypothesis that MS patients have gut microbial dysbiosis and further study is needed to better understand their role in the etiopathogenesis of MS.
Keywords: Male; Gastrointestinal Microbiome; Gastrointestinal Tract; Humans; mužské pohlaví; Female; RNA ribozomální 16S; roztroušená skleróza; ženské pohlaví; RNA, Ribosomal, 16S; mikrobiota; Multiple Sclerosis; Adult; Dysbiosis; dysbióza; gastrointestinální trakt; Microbiota; dospělí; lidé; střevní mikroflóra